Thioester‐Assisted Sortase‐A‐Mediated Ligation. Issue 28 (19th May 2022) - Zuo, Chong; Ding, Ruichao; Wu, Xiangwei; Wang, Yuanxia; Chu, Guo‐Chao; Liang, Lu‐Jun; Ai, Huasong; Tong, Ze‐Bin; Mao, Junxiong; Zheng, Qingyun; Wang, Tian; Li, Zichen; et al.
Abstract: Sortase A (SrtA)‐mediated ligation, a popular method for protein labeling and semi‐synthesis, is limited by its reversibility and dependence on the LPxTG motif, where "x" is any amino acid. Here, we report that SrtA can mediate the efficient and irreversible ligation of a protein/peptide containing a C‐terminal thioester with another protein/peptide bearing an N‐terminal Gly, with broad tolerance for a wide variety of LPxT‐derived sequences. This strategy, the thioester‐assisted SrtA‐mediated ligation, enabled the expedient preparation of proteins bearing various N‐ or C‐terminal labels, including post‐translationally modified proteins such as the Ser139‐phosphorylated histone H2AX and Lys9‐methylated histone H3, with less dependence on the LPxTG motif. Our study validates the chemical modification of substrates as an effective means of augmenting the synthetic capability of existing enzymatic methods. Abstract : Sortase A was found to mediate the efficient and irreversible ligation of a protein/peptide containing a C‐terminal thioester with another protein/peptide bearing an N‐terminal Gly, with broad tolerance for a wide variety of LPxT‐derived sequences. The thioester‐assisted SrtA‐mediated ligation strategy enabled the expedient preparation of proteins bearing various N‐ or C‐terminal labels and post‐translationally modified proteins.